Penerapan Algoritma K-Means Clustering untuk Melihat Hubungan Kegiatan Tahfiz dengan Hasil Belajar - Asri Hidayad; Sarjon Defit; S Sumijan (Rektorat Universitas Putra Indonesia YPTK Padang, 2020)
The purpose of this study is to evaluate whether Tahfiz activities and learning outcomes are effective or not. The data processed in this study were data on tahfiz activities and data on student learning outcomes in class XI (eleven) totaling 42 data sourced from memorization of tahfiz, tahfiz grades, and student grades in Madrasah Aliyah Negeri 1 Bukittinggi. Based on the analysis of the data, this classification uses one of the methods of the Data Mining algorithm, K-Means Clustering. K-Means Clustering algorithm works based on the grouping method, In this data mining technique consists of data testing and training data with the input of the number of memorization of tahfiz, and the value of tahfiz as well as learning outcomes. The results of this study the school can determine how influential this activity tahfiz on student grades.